Physical Fitness and the Level of Pain Intensity in Adolescents: A School-based Study - Zvonar, Martin; Kasović, Mario; Štefan, Lovro (International journal of environmental research and public health, 2019)
Background: The main aim of the study was to explore the association between objectively measured physical fitness and the level of pain intensity. Methods: In this cross-sectional study, we included 1036 adolescents (mage ± SD = 16.3 ± 1.1 years; mheight ± SD = 1.74 ± 0.1 m; mweight ± SD = 64.7 ± 12.4 kg; mbody-mass index ± SD = 21.3 ± 3.0 kg/m2) from 11 secondary schools located in the city of Zagreb (Croatia). Physical fitness was determined by using waist circumference, sit-ups in 1 min, standing long jump and sit-and-reach tests. Overall physical fitness index was calculated by summing the z-score values of each physical fitness test. The level of pain intensity was assessed with the Numeric Pain Rating Scale, a one-dimensional measure of pain intensity. Associations were calculated with correlation analyses. Results: In boys, pain intensity was associated with sit-ups in 1 min (r = -0.16, p < 0.001), standing long jump (r = -0.14, p = 0.003) and overall physical fitness index (r = -0.13, p = 0.004), while no significant associations with waist circumference (r = 0.04, p = 0.438) and sit-and-reach test (r = -0.01, p = 0.822) were observed. In girls, pain intensity was associated with standing long jump (r = -0.17, p < 0.001) and overall physical fitness index (r = -0.10, p = 0.018), while no significant associations with waist circumference (r = 0.01, p = 0.735), sit-ups in 1 min (r = -0.06, p = 0.126) and sit-and-reach test (r = -0.05, p = 0.232) were observed. When we adjusted for self-rated health, sleep duration, smoking status, alcohol consumption, screen-time and psychological distress, similar associations remained. Conclusions: Our study shows a weak association between physical fitness and pain intensity in a large sample of adolescents. Although a cross-sectional design, health-professionals should use physical fitness as a screening tool to assess the level of pain intensity.
Keywords: Physical Fitness; index tělesné hmotnosti; obvod pasu; Cross-Sectional Studies; Croatia; Cities; Waist Circumference; cvičení; mladiství; mužské pohlaví; tělesná výkonnost; průřezové studie; Chorvatsko; Body Mass Index; dítě; Pain Measurement; měření bolesti; Body Weight; Child; ženské pohlaví; Humans; školní zdravotnické služby; tělesná hmotnost; School Health Services; velkoměsta; Exercise; Female; Adolescent; lidé; Male